Herdabalidade correlações do rendimento com seus componentes, em dois cruzamentos de feijão - dos Santos, Pedro César; Cardoso, Antônio Américo; Vieira, Clibas; Silva, José Carlos (Revista Ceres, 2025)
Heritabilities and correlation coefficients between yield and the yield components were calculated in two Phaseolus vulgaris crosses: ’Preto Sessenta Dias 40’ x ‘Ricopardo 896’ and ‘Preto Sessenta Dias 53’ x ‘Ricopardo 896’.